Aspidosperma brasiliense (Apocynaceae), a new and widely distributed species - de Souza Pereira, Andreza Stephanie; Devides Castello, Ana Carolina; Scudeler, Ana Laura; Olmos Simões, André; Koch, Ingrid (Phytotaxa, 2017)
Aspidosperma brasiliense, a new species from Brazil and widely distributed in the country, is described and illustrated here. A comparative table based on morphological data and an identification key to Aspidosperma brasiliense and its related species are also provided.